Serological response to anti-rabies vaccination in animals: Failure to achieve protective antibody level - MUGALE, MADHAV; SANDHU, B S; RAI, T S; SINGH, C K; SOOD, N K (The Indian Journal of Animal Sciences, 2013)
The present study was conducted to elucidate the serological response in 183 rabies suspected cases of small and large animals presented Veterinary Clinical Complex from July 2010 to June 2011. Immune status was assessed by ELISA. Out of 183 cases, 180 were dogs and 3 large animals. In vaccinated dogs, rabies virus specific antibodies (0.5IU/Î¼l) were detected in 70.55% (115/163) cases. Whereas 29.44% vaccinated dogs did not reveal protective rabies titre. None of the unvaccinated dogs and large animals showed protective rabies specific antibody titre. The antibody level was directly proportional to the number of vaccine shots. Vaccination in dewormed animals revealed better protection and antibody titre (8.878 IU/Î¼l) than non-dewormed animals (4.01 IU/Î¼l). However, no significant difference in the rabies antibody titre among the sexes was observed.